PERAN BUDAYA KERJA, PENGEMBANGAN KARIR DAN TATA RUANG KERJA TERHADAP KEPUASAN KERJA KARYAWAN BANK MANDIRI SURAKARTA - Putro, Andy Nugroho (2011)
Research purpose is analyzing work culture, career development, and spatial working roles to Mandiri Bank Surakarta workers work satisfaction. The study took place at Bank Mandiri Surakarta, which is located on Jalan Slamet Riyadi 325 Surakarta. With a population of 205 employees. Samples taken as many as 30% of the total population, or by 62 respondents. The sampling technique used in this study were incidental sampling technique. The analysis technique used is logistic regression analysis model. The results of this study were (1) work culture variable has significant role to worker work satisfaction proved by wald value as 8,019 and significant value as 0,005 < 0,05. (2) caree development variable has significant contribution to work satisfaction proved by wald value as 5,341 and significant value as 0,021 < 0,05. (3) spatial working variable has significant contribution to work satisfaction proved by wald value as 6,315 with significant value as 0,012 < 0,05. (4) B expectation test result or Exp (B) shows that work culture and spatial work variables have the biggest role to Mandiri Bank Surakarta workers work satisfaction. It is shown by Exp value (B) work culture variable as 1,241 is the biggest than career development and spatial working variables.